Analisis Kesalahan Menulis Bahasa Arab Pada Pembelajaran Imla Murid Kelas 2 Ula Madrasah Diniyah Darussalam Padar Kesamben Ngoro Jombang - Rifki Ramadani; Mohamad Yahya Ashari; Andik Wahyun Muqoyyidin (Jurnal Teologi Islam, 2026)
The purpose of this study was to analyze Arabic writing errors, analyze the learning of dictation (imla'), and determine how teachers evaluate Arabic writing errors in Grade 2 Ula students at Madrasah Diniyah Darussalam Padar Kesamben Ngoro Jombang. This research used a descriptive qualitative research method, analyzing through a documentary study approach. The data collection techniques used were interviews, observation, and documentation. In the implementation, the teacher wrote the material on the board, explained it, conducted a question and answer session, then dictated simple vocabulary words that were repeated three times before the students wrote them in their notebooks. The teacher evaluated Arabic writing errors by collecting error data, identifying errors, classifying errors, and correcting student errors to provide appropriate guidance. The results showed that many students still made errors, such as errors in connecting letters, letter usage, letter length, and letter omissions and additions. Errors in writing Arabic among second-grade Ula students at Madrasah Diniyah Darussalam Padar Kesamben Ngoro Jombang are caused by a lack of mastery of basic Arabic writing skills, limited learning media, and the use of traditional teaching methods. The imla’ learning process is carried out through the dictation method, beginning with the teacher writing and explaining the material on the board, then dictating simple Arabic vocabulary three times for students to write down. Evaluation is conducted by collecting, identifying, classifying, and correcting students’ mistakes, and the results show that many students still make errors in writing Arabic. This evaluation also serves as a reference for teachers to understand students’ writing abilities and their comprehension of the material taught.